Online and in-person student experiences on the PDBA programme at Wits Business School - Horo, Sibongile Lungelwa (University of the Witwatersrand, Johannesburg, 2023)
This study explores Wits Business School’s (WBS) students, alumni and course administrators’ perceptions of online learning compared to the classroom learning experience in the Post Graduate Diploma in Business Administration (PDBA) programme. A concurrent mixed methods design was followed in this study whereby quantitative and qualitative methods were employed in data collection and analysis. The study sampled 107 WBS students with experiences with both online learning and in-person classroom learning. Two course administrators and two students were also sampled to explore their perceptions of the two forms of course delivery. The study also intended to assess how these experiences influence students’ satisfaction with learning. Descriptive analysis and deductive analysis were utilised for data analysis for both quantitative and qualitative phases of the study respectively. The results from the survey found that students have more favourable perceptions of online learning in comparison to traditional learning. However students had less favourable perceptions with online learning in terms of student- to-student interaction. Regression analysis revealed that online learning significantly improves student satisfaction through student-instructor and student- content interaction. Results showed that satisfaction with online learning was positively influenced by favourable perceptions of interactions between students and lecturers and students with the course content. There was no evidence to conclude that traditional face-to face learning positively influences student satisfaction with learning. However, the course administrators did not see lack of student-student interaction as a key issue that may influence the performance and satisfaction of students with the courses. The results of the study recommend the implementation of a hybrid leaning model to improve both online and traditional learning.
A research article submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Master of Management in the field of Business Administration Johannesburg, 2023
Keywords: Online learning; Traditional face to face learning; Student experiences; Concurrent mixed methods design; UCTD; SDG-8: Decent work and economic growth